Towards the characterization of silicon surfaces: solid state nuclear magnetic resonance studies - Caylor, Rebecca Anne, author; Maciel, Gary E., advisor; Bernstein, Elliot, committee member; Van Orden, Alan, committee member; Watson, Ted, committee member; Prieto, Amy, committee member (Colorado State University. Libraries, 2011)
One of the developing areas in silicon chemistry is in small silicon particles, primarily the nanoparticles regime. When on the 'nano' scale, silicon possesses very different properties and characteristics from bulk silicon. These properties include novel optical and electronic properties that are size dependent. Semiconductor nanoparticles possess a unique bright photoluminescence when in the nanoparticle regime. The photoluminescence in the nanoparticle regime answers the problem of inefficient emissions, which have previously been a problem in bulk silicon, for use in solar cells. Nanoparticle silicon (np-Si) is also biocompatible, allowing for the use in various biological applications including biological tracers, biosensors, delivery of medicine, as well as many others. Although np-Si is widely used, its surface structure still remains largely debated. The surface structure of np-Si is of critical importance as it affects the reactivity of the sample as well as the properties the samples possess. Relative to other silicon samples, np-Si lends itself to be studied by solid state NMR due to its higher surface area, although other types of silicon samples have been studied to some degree in this dissertation project. The surface structure and adjacent interior of np-Si, obtained as commercially available silicon nanopowder, were studied in this project using multinuclear, solid-state NMR spectroscopy. The results are consistent with an overall picture in which the bulk of the np-Si interior consists of highly ordered ('crystalline') silicon atoms, each bound tetrahedrally to four other silicon atoms. From a combination of 1H and 29Si magic-angle-spinning (MAS) NMR results and quantum mechanical 29Si chemical shift calculations, silicon atoms on the surface of 'as-received' np-Si were found to exist in a variety of chemical structures, including primarily structures of the types (Si-O-)n(Si-)3-nSi-H (with n = 1 - 3) and (Si-O-)2Si(H)OH, where Si stands for a surface silicon atom and Si represents another silicon atom that is attached to Si by either a Si-Si bond or a Si-O-Si linkage. The relative populations of each of these structures can be modified by chemical treatment, including with O2 gas at elevated temperature. A deliberately oxidized sample displays an increased population of (Si-O-)3Si-H, as well as (Si-O-)3SiOH sites. Considerable heterogeneity of some types of surface structures was observed. A comparison of 29Si and 1H MAS experiments provide strong evidence for a modest population of silanol (Si-OH) moieties, along with the dominant Si-H sites, on the surface of 'unmodified' np-Si; the former moieties are enhanced by deliberate oxidation of the sample. Dipolar-dephasing experiments provide further evidence of Si-H sites on the surface.
Keywords: silicon nanoparticles; solid state nuclear magnetic resonance